A formação da consciência no contexto pós-moderno: uma análise da cristologia de José Mª. Castillo como proposta para uma ética cristã renovada - Moraes, Karolayne Maria Vieira Camargo de (2023)
The present research aims to analyze the conscience’s process formation in the post-modern context, making use of the Christology developed by José María Castillo as a methodological reference that enables the development of a renewed Christian ethics. It’s known that the only fact of denominating the contemporary reality as “postmodern”, by itself, corresponds to a complex question, because of the difficulty to synthetize and to express in a single word many phenomena ongoing nowadays. Nevertheless, it’s consensual to many scholars the implementation of an association between neoliberal logic and digital media as determinant fact on all areas of the society and human life, that promotes an unprecedented influence on the formation of consciences. In face of this reality, the exercise of autonomy and freedom’s individuals in current society is questioned. In this regard, the Christology of José María Castillo presents Jesus of Nazareth’s life as a paradigm able to illuminate the mystery of human being, highlighting its dignity and its calling for humanization as criteria to social life. The ethical principles followed by Jesus thus become decisive in a renewed Christian ethics proposal, oriented by its sources and sensitive to the signs of the times, as Vatican Council II requests to Moral Theology, aiming to think of new economic logic and an integral education. In this way, the research seeks to problematize which path(s) are possible to the formation of Christian conscience on contemporary in three stages: in the first one, seeks to understand contours of the so-called postmodern reality; in the following one, verifies how José María Castillo’ Christology can illuminate the formation of conscience’s process, offering important ethical principles; in the last one, how these principles can be assumed and shape the contemporary individuals’ conscience and life, as through overcoming pessimism, freedom assumption and the joining of forces to change reality endorsing, for example, the current pontificate’s efforts in seek of a new face to economy and an integral e communitarian education of individual